The impact of a reform: Limitation of autonomy, narrowing of freedom, and erosion of participation - Prieto, Miriam; Villamor, Patricia (Education Policy Analysis Archives, 2018)
Educational systems across the world are applying measures addressed to the improvement of education quality. These measures have as a consequence, the shaping of a rhetoric that works as a framework for the interpretation of educational agents’ action. The article deals with the analysis of the impact of global educational policies on the notions of educational agents’−teachers and parents−autonomy, freedom and participation, within the Madrilenian educational system. To this end, it takes as a context the meaning given to these notions within the Spanish educational system, through the analysis of its evolution over the national education laws. Next, it presents the reform applied to the Madrilenian educational system through facing the policy makers’ speeches and the educational legislation that they have enacted. The results show that the impact of the reform leads to the limitation of teachers’ autonomy, the erosion of parents’ participation and the narrowing of parents’ freedom.